The Measurement of Excess Burden with Explicit Utility Functions - Rosen, Harvey S. (Journal of Political Economy, 1978)
[The excess burden of a tax is the diminution of utility above that which would have occurred had the tax been collected as a lump sum. Usually, excess burden is measured by a method which relies on a second-order approximation to an arbitrary utility function. In this paper, excess burdens are computed using explicit utility functions and the results compared with those obtained from the second-order approximation.]